PENGARUH DEBT TO EQUITY RATIO, CASH RATIO DAN DIVIDEND PAYOUT RATIO TERHADAP HARGA SAHAM LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Olivia Dewanti (RISTANSI: Riset Akuntansi, 2022)
This study aims to determine and analyze the effect of debt to equity ratio, cash ratio and dividend payout ratio on stock prices. The research method used is quantitative. A total of 54 sample data were determined by purposive sampling method. data analysis technique using multiple linear regression analysis. The results of the t test show that the independent variables debt to equity ratio, cash ratio and dividend payout ratio have no significant effect on stock prices, because LQ45 Company is a company that is highly trusted by the public so that information from DER, CR and DPR will not affect investment decisions.